2005
DOI: 10.1111/j.1600-0404.2005.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache characteristics in obstructive sleep apnea syndrome and insomnia

Abstract: Headache is a common finding in both OSAS and insomnia patients. Because morning headache seems to be more specific for OSAS than insomnia, and in OSAS its occurrence seems to be associated with disease severity, we hypothesize the involvement of certain pathogenic mechanisms associated with OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 34 publications
2
53
2
4
Order By: Relevance
“…There is, however, some indication that a sizeable proportion of apneic patients with awakening headache would not fulfill the new criteria. In fact, headache coinciding with sleep apnea may present as migraine, tension, cluster, or nonspecific other headache disorder [31].…”
Section: Sleep Apnea Headachementioning
confidence: 99%
“…There is, however, some indication that a sizeable proportion of apneic patients with awakening headache would not fulfill the new criteria. In fact, headache coinciding with sleep apnea may present as migraine, tension, cluster, or nonspecific other headache disorder [31].…”
Section: Sleep Apnea Headachementioning
confidence: 99%
“…There is some indication that a sizeable proportion of apneic patients with awakening headache would not fulfill the new criteria. Alberti et al (9) observed that sleep apnea headache may present as: migraine, tension, cluster, or unclassifiable; bilateral (53%) or unilateral (47%); located frontal (33%), frontotemporal (28%), or temporal (16%); with pressing/tightening pain in the majority of patients (79%); with intensity mild (47%), moderate (37%) or severe (16%). Headaches remitted within 30 minutes of waking in only 40% of cases.…”
mentioning
confidence: 99%
“…Although, International Classification of Headache Disorders, second edition (ICHD-II) classifies headache attributed to OSAS as headache attributed to impaired homeostasis [8], several reports revealed that the headache prevalence in OSAS varies between 11% -40% [6] [10]. The most frequent headaches reported in OSAS patients include morning headaches of tension-type, chronic daily headaches, exacerbation of migraine, or cluster headaches [6] [11] [12].…”
Section: Discussionmentioning
confidence: 99%